(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2019)
Background: With rapid technological changes in the field of food safety, we are moving away from traditional means of cooking and preservation to highly advanced mechanisms and procedures like Sous Vide, High Temperature Short Timing, Irradiation Techniques etc. These changes also bring growth of hospitality industries such as international and national tourism, restaurants, fast-food outlets and catering businesses. Objective: To gain knowledge about the preferences of the customers about food and its safety and secondly to examine the current status of Food and Hygiene standards in popular Quick Service Restaurants (QSRs). Methodology: The whole research has been conducted by surveying the opinions of 50 customers regarding their food habits, preferences, awareness about food safety laws. Fast food from popular fast food QSRs were tested for contamination. Results: The research revealed that while 53% of the respondents checked the hygiene of the outlet they ate in, yet 67% were unaware of the food safety laws in the country. The food samples had negligible contamination except for sample A that had 15 CFU/10ml. Conclusion: The research concluded that the consumers need to be made aware and they also need to have some technical information related to the said subject.